ARCHITECTURAL PHILOSOPHY OF THE AL-KAMIL MOSQUE BUILDING IN THE JATIGEDE RESERVOIR, SUMEDANG CITY: APPLYING THE LOTUS FLOWER SHAPE TO THE MOSQUE DOME - Nurlestya, Putri Yastine (Journal of Development and Integrated Engineering, 2023)
Jatigede Reservoir is a tourist development destination inSumedang City, one of the newest of which is the Al-KamilMosque which is located on Panenjoan Hill, Sumedang City.The design of this mosque was conceptualized by West JavaGovernor Ridwan Kamil. This research aims to identify thephilosophy of architectural form in the Al-Kamil Mosque,Sumedang City by exploring the symbolization of the formand visual characteristics of the application of the tulip flowershape applied to the mosque dome. This research uses aqualitative descriptive method by identifying, comparing,and tracing characteristics through conceptual documents ofthe Al-Kamil Mosque, especially in the form of idea sketches,planning documents, and observations of the physicalmosque building. So it can be concluded that 1)With a periodcomposition that has an approach to the process of ablooming lotus flower, it signifies the vision and mission ofSumedang City, 2) A dome that rises high, the shape of thedome of the Al-Kamil mosque is an application of the shapeof a lotus flower that is in the bud, the shape of this lotusflower can be interpreted as a symbol of gratitude like thephilosophical meaning of the lotus flower, namelyabundance, and prosperity, 3) The shape of the canopy of thismosque building has an approach to the shape of a flowercrown, the function of this lotus flower crown is the same as the canopy at the Al-Kamil mosque, namely to protect mosque congregation who are praying or visiting, 4) Thecolor of this mosque is given as white, which means clean andholy, as people who enter the mosque are clean and holy.